“CORE” a new assay for rapid identification of Klebsiella pneumoniae COlistin REsistant strains by MALDI-TOF MS in positive-ion mode - Foglietta, Gianluca; De Carolis, Elena; Mattana, Giordana; Onori, Manuela; Agosta, Marilena; Niccolai, Claudia; Di Pilato, Vincenzo; Rossolini, Gian Maria; Sanguinetti, Maurizio; Perno, Carlo Federico; Bernaschi, Paola (Frontiers in Microbiology, 2023)
Due to the global spread of pan resistant organisms, colistin is actually considered as one of the last resort antibiotics against MDR and XDR bacterial infections. The emergence of colistin resistant strains has been observed worldwide in Gram-negative bacteria, such as Enterobacteriaceae and especially in K. pneumoniae, in association with increased morbidity and mortality. This landscape implies the exploration of novel assays able to target colistin resistant strains rapidly. In this study, we developed and evaluated a new MALDI-TOF MS assay in positive-ion mode that allows quantitative or qualitative discrimination between colistin susceptible (18) or resistant (32) K. pneumoniae strains in three hours by using the “Autof MS 1000” mass spectrometer. The proposed assay, if integrated in the diagnostic workflow, may be of help for the antimicrobial stewardship and the control of the spread of K. pneumoniae colistin resistant isolates in hospital settings.